Development of a Rapid and Sensitive HPLC Assay Method for Lenalidomide Capsules and Its Related Substances - L. Maheshwara Reddy; K. Janardhan Reddy; L. Bhaskar Reddy; P. Raveendra Reddy (E-Journal of Chemistry)
A chromatographic method was established for the determination of lenalidomide and related substances in 10 mg and 5 mg capsules using Sunfire C-18(250×4.6 mm ID, 5 μm) HPCL column with 85:15 v/v ratio of mobile phases A (mixture of phosphoric acid buffer and 1-octane sulphonic acid sodium salt) and B(55: 45 v/v ratio of methanol and acetonitrile) at 40°C and 210 nm wave length. The degradation studies were performed using 0.1N HCl, 0.1 N NaOH, 1% v/v hydrogen peroxide, humidity, UV at 254 nm, Sun light, and heat to 60°C. No significant degradation of lenalidomide was observed. However, the slight degradation was observed in presence of NaOH. The developed HPLC method gave the peaks purity angle was less their threshold angle, indicating it to be suitable for stability studies. It was validated with respect to linearity, accuracy, precision, ruggedness, and robustness.